2017
DOI: 10.18632/oncotarget.20772
|View full text |Cite
|
Sign up to set email alerts
|

Association of ADAM12 gene polymorphisms with knee osteoarthritis susceptibility

Abstract: Previous studies that evaluated the association between a disintegrin and metalloprotease 12 (ADAM12) gene polymorphisms and knee osteoarthritis (KOA) have given controversial and indefinite results. Therefore, we performed a meta-analysis to confirm this correlation. We searched the PubMed, Embase, and SinoMed databases for all papers published up to April 11, 2017. Overall, five different studies, totaling 2,353 cases and 3,668 controls, were retrieved on the basis of the search criteria for KOA susceptibili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 28 publications
1
8
0
3
Order By: Relevance
“…Over the last years, different genetic studies have been performed to identify genes that encode for proteins associated with OA susceptibility. From these, the rs3740199 (c.142G> C) polymorphism of ADAM12 gene had been previously associated with KOA in a Thai male population (Poonpet et al, 2016); likewise, several meta-analyses have reported this association (Hu et al, 2017;Ren et al, 2017;Wu et al, 2017). However, we did not find any association for rs3740199 ADAM12 polymorphism in our study, in agreement with other authors (Limer et al, 2009;Kerna et al, 2013;Lou et al, 2014;Wang et al, 2015).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Over the last years, different genetic studies have been performed to identify genes that encode for proteins associated with OA susceptibility. From these, the rs3740199 (c.142G> C) polymorphism of ADAM12 gene had been previously associated with KOA in a Thai male population (Poonpet et al, 2016); likewise, several meta-analyses have reported this association (Hu et al, 2017;Ren et al, 2017;Wu et al, 2017). However, we did not find any association for rs3740199 ADAM12 polymorphism in our study, in agreement with other authors (Limer et al, 2009;Kerna et al, 2013;Lou et al, 2014;Wang et al, 2015).…”
Section: Discussionsupporting
confidence: 92%
“…On the contrary, the CC genotype of rs1871054 polymorphism of ADAM12 gene had also been associated with an increased risk for susceptibility to KOA in a Chinese Han population (Lou et al, 2014;Wang et al, 2015). Several meta-analysis studies have also found an association with this polymorphism (Hu et al, 2017;Lv et al, 2017;Ren et al, 2017;Chen et al, 2018). Also, in an Estonian population, the C allele was associated with advanced grades of KOA (Kerna et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, single genes or single environmental factors may not be likely to have direct effects on PCOS susceptibility, but complex interactions between genetic and environmental factors may be involved in the disease development. The last but not the least, if numbers of included studies were small, false-negative results may be detected for each polymorphism [41].…”
Section: Discussionmentioning
confidence: 99%
“…The candidates have been selected predominantly according to the principle that the product they code for is regulators of both joint formation and maintenance. [ 11 ] A great many of polymorphisms in various genes such as ESR1 , [ 12 , 13 ] VDR , [ 14 , 15 ] ADAM12 , [ 16 , 17 ] MMP3 , [ 18 ] and Asporin [ 19 ] have been demonstrated to be related with risk of OA.…”
Section: Introductionmentioning
confidence: 99%